TO ASSESS THE ROLE OF NATURAL PESTICIDES MADE FROM TULSI OCIMUM TENUIFLORUM, TURMERIC CURCUMA LONGA AND NEEM AZADIRACHTA INDICA ON CULINARY CROPS AND ITS MATURING SOIL - Gupta, Deeksha; Sivadas, Shilpa; Vikram, Keerthi; V., Suneetha (International Journal of Applied Pharmaceutics, 2016)
Objective: Our research plans on creating natural pesticides to serve the same along with keeping it sustainable, effective and healthy. Our project aims to find the effects of natural pesticides like neem, tulsi and turmeric on plants like mung bean, chickpea, methi (fenugreek) and other varieties. We also aim to provide a solution from all the other techniques that have been exhaustively implied and are being created to ensure the fulfillment for the future generations, e. g. GMO Methods: The extracts of neem, tulsi and turmeric are made by grinding and mixing it with water in 1:1 ratio and are then categorically sprayed over a range of 12 pots separated according to different types of plants namely mung, methi and channa. The growth of the plants and the soil analysis (by serial dilution) is done over the microbial growth, resistance to fungal infections and other pest infestations. Results: We came up with a positive result showing less chance of infections and decrease in the colonies of harmful bacteria and pathogens with the help of serially diluting the soil sample under the effect of natural pesticides and pore plating it on the media. Conclusion: The plants exposed to the natural pesticides showed better resistance and growth overall. Keywords:, Biological magnification, GMO, Carcinogenic, Serial dilution